PEGylated 2D-nanomaterials alleviate Parkinson's disease by shielding PIP2 lipids to inhibit IP3 second messenger signaling. (October 2022) - Huang, Liwen; Zhang, Xiao; Ding, Zhaowen; Qi, Yilin; Wang, Wenjing; Xu, Xihan; Yue, Hua; Bai, Lihuan; Wang, Heping; Feng, Leyan; Ren, Jing; Yang, Xue; et al.
Abstract: Researches on nano-bio interfaces have revealed that two-dimensional (2D) nanomaterials can form functionally impactful architectures upon interaction with biological membranes. These biological impacts may drive various changes of membrane phospholipids, raising the possibility of alleviating neurodegenerative disorders by specifically altering metabolism of membrane phospholipids. Here, we demonstrate that PEGylated 2D nanomaterials including graphene oxide and poly-L -lactic acid sheets (denoted as P-sheet) alleviate behavioral and neuronal degeneration of Parkinson's disease (PD). Upon this finding, we experimentally identify enrichment for the phosphatidylinositol-4, 5-bisphosphate (PIP2 ) lipid interacting with P-sheet and reveal the underlying mechanism by molecular dynamics simulations: a flip-flop orientation shift of PIP2 lipids within the membrane restricts the hydrolysis site, preventing cleavage-mediated inositol 1, 4, 5-trisphosphate. As a result, Ca 2+ -related endoplasmic reticulum stress can be reduced to protect the neurons of PD mice. These results together support P-sheet nanomaterials as a new type of drug-free agent for selective modulation of neurodegenerative-disorder-associated membrane-lipid dysregulation and potential PD therapy. Graphical Abstract: PEGylated 2D nanosheets including graphene oxide and poly-L-lactic acid sheets (denoted as P-sheet) were used as modulators of nerve cell membrane phospholipid remodeling to treat Parkinson's disease. This strategy induced the amplification of downstream cascades through nano-bio interaction in a low-dose drug-free manner, which in turn drove "flip-flop switching" of PIP2's orientation, inhibited endoplasmic reticulum stress and neuronal damage, to relieve Parkinson's disease effectively. ga1 Highlights: P-sheet can form special nano-bio interface with nerve cell membrane, achieving the therapeutic effect on PD. P-sheet shields the hydrolysis site of PIP2 on the nerve cell membrane to mediate the downstream signal transduction. Such therapeutic effect can be extended to the FDA-approved biodegradable PEGylated Poly(L-lactide acid) sheet.